2019
DOI: 10.1182/blood-2019-124150
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Diagnosis to Treatment Interval on the Outcome of Patients with Acute Myeloid Leukemia

Abstract: Introduction: Acute myeloid leukemia (AML) has historically been considered an oncologic emergency, requiring immediate intervention and initiation of therapy. Although urgency to initiate treatment has been debated, no guidelines exist to address the impact of diagnosis to treatment interval (DTI) in patients with AML. Recent FDA approvals have added treatment options using targeted therapy as monotherapy in older patients (e.g. - ivosidenib), or in combination with chemotherapy in younger pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Interestingly, no studies that examined the effect of TDT on ED found a significant association 5,6,17 . Similarly, studies that looked at 30‐, 60‐, or 90‐day mortality did not find a significant association with TDT 7,9,20 . One nonrandomized prospective trial found that 30‐day mortality was significantly lower in patients who opted to delay treatment initiation by up to 7 days in pursuit of targeted therapy compared to those receiving the standard of care 23 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, no studies that examined the effect of TDT on ED found a significant association 5,6,17 . Similarly, studies that looked at 30‐, 60‐, or 90‐day mortality did not find a significant association with TDT 7,9,20 . One nonrandomized prospective trial found that 30‐day mortality was significantly lower in patients who opted to delay treatment initiation by up to 7 days in pursuit of targeted therapy compared to those receiving the standard of care 23 .…”
Section: Resultsmentioning
confidence: 99%
“…5,6,17 Similarly, studies that looked at 30-, 60-, or 90-day mortality did not find a significant association with TDT. 7,9,20 One nonrandomized prospective trial found that 30-day mortality was significantly lower in patients who opted to delay treatment initiation by up to 7 days in pursuit of targeted therapy compared to those receiving the standard of care. 23 However, it is possible that these therefore it is possible that they underestimate the true effect of chemotherapy delay on the rate of early death.…”
Section: Association Of Tdt With Mortalitymentioning
confidence: 99%